ANALISIS KESALAHAN SISWA DALAM MENGERJAKAN SOAL PADA MATERI BILANGAN BULAT - Wicaksono, Fitra Dwi; Andriati, Lissa (Journal of Technology, Mathematics and Social Science, 2022)
The purpose of this research is to analyze students' mistakes in working on questions on integer material. This type of descriptive research, as well as data analysis techniques in this study include checking test results, analyzing student answers, and at each stage or step of solving the problem to get an error score (if there is an error). There are five steps of analysis work, namely: collecting research samples; fault identification; error explanation; classifying errors, and evaluating errors. The research instrument was in the form of a written test in the form of a field consisting of 10 questions. Each number was given a score of 1. This research was conducted by giving a test in the form of 10 questions on integer arithmetic operations to class VII students of junior high school. The test results were analyzed to see the types of mistakes made by students. Furthermore, several students were selected who had errors in working on the questions. There were several mistakes made by the subject in solving math problems. The error was made by the subject with different indicators.Keywords: Mathematics; number; error analysis;